PENINGKATAN KUALITAS MASYARAKAT DESA PEGUYANGAN KAJA MELALUI BUDAYA GOTONG ROYONG - Mirah Purnama Sari A.A Pt. Agung (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2023)
Kuliah Kerja Nyata (KKN) Program is carried out with the aim of growing awareness and empathy for Warmadewa University students towards the real problems faced by rural communities, and also to realize community welfare and educate the nation's life and to promote sustainable development. This KKN activity is located in Peguyangan Kaja Village, North Denpasar District, Denpasar City, Bali Province. Peguyangan kaja village office is located on Jl. North Ahmad Yani No. 456, Peguyangan Kaja, North Denpasar, Denpasar City. Kuliah Kerja Nyata-Pembelajaran Pemberdayaan Masyarakat (KKN-PPM) UNWAR in Peguyangan Kaja Village is Group 2 and consists of 30 students. The approach system used is direct observation and deliberation. The solutions provided by KKN-PPM UNWAR students are as follows: 1) participating in "Clean Friday" and other hygiene activities, 2) distributing free masks and socializing the community around Peguyangan kaja village about the dangers of the omicron type of covid-19 virus, 3 ) assisting Posyandu activities for toddlers and the elderly as well as providing additional food in Peguyangan Kaja Village, 4) Implementation of the Stunting Case Prevention Program, 5) Marketing of local UMKM products through Social Media and the benefits of mushrooms for health, 6) Implementation of the Delivery of Jempiring Plants to Each Head of Dusun, 7) Implementation of Flowering Plant Planting Activities in Peguyangan 6 Elementary School Area, 8) 3rd dose vaccination activity for people in Peguyangan Kaja Village.